Printing - Nicholson, Sue. (London : QEB Pub., 2005)
Presents step-by-step, photo-illustrated instructions for making prints with hands, fingertips, leaves, food, string, "junk" such as nails and spools, stencils, and design blocks, and for making monotypes and marbled prints.
"Create amazing pictures with paper, paint, and a palette"--Cover.
Includes index.
4.8
K-3.
K-3
Keywords: Printing -- Technique -- Juvenile literature; Printing -- Technique; Printing -- Technique